Astaxanthin from shrimp by-products for active packaging - Sanches-Silva, A. (2013)
This work was funded under Project no. 95935 by FONCICYT C002-2008-1/ALA – 127 249. The authors are grateful for the postdoctoral contract of Ana Sanches Silva in the frame of the Program ‘Science 2007’, funded by Fundação para a Ciência e a Tecnologia, Portugal.